Design, Spectral Insights, and Enhanced Antioxidant Potential of Novel Phenothiazine Derivatives-1 - Singh, Shamsher; Sharma, Himanchal; Gohri, Smiriti; Taumer, Dhananjay (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2026)
<span class=
Keywords: 10-chloroacetylphenothiazine